2016
DOI: 10.1021/acs.est.5b05099
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based NO2 and Model Validation in a National Prediction Model Based on Universal Kriging and Land-Use Regression

Abstract: Epidemiological studies increasingly rely on exposure prediction models. Predictive performance of satellite data has not been evaluated in a combined land-use regression/spatial smoothing context. We performed regionalized national land-use regression with and without universal kriging on annual average NO2 measurements (1990–2012, contiguous U.S., EPA sites). Regression covariates were dimension-reduced components of 418 geographic variables including distance to roadway. We estimated model performance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 32 publications
6
117
0
1
Order By: Relevance
“…OMI NO 2 data have been used in a number of recent health studies (e.g., Hystad et al, 2011Hystad et al, , 2012Novotny et al, 2011;Prud'homme et al, 2013;Vienneau et al, 2013;Knibbs et al, 2014;Hoek et al, 2015;Belche et al, 2015;Crouse et al, 2015;de Hoogh et al, 2016;Young et al, 2016). For example, Belche et al (2013) found that annual OMI NO 2 column density data correlate well (r = 0.93) with surface data in southern California and provide a reliable measure of spatial variability for NO 2 exposure assessment.…”
Section: Nomentioning
confidence: 99%
“…OMI NO 2 data have been used in a number of recent health studies (e.g., Hystad et al, 2011Hystad et al, , 2012Novotny et al, 2011;Prud'homme et al, 2013;Vienneau et al, 2013;Knibbs et al, 2014;Hoek et al, 2015;Belche et al, 2015;Crouse et al, 2015;de Hoogh et al, 2016;Young et al, 2016). For example, Belche et al (2013) found that annual OMI NO 2 column density data correlate well (r = 0.93) with surface data in southern California and provide a reliable measure of spatial variability for NO 2 exposure assessment.…”
Section: Nomentioning
confidence: 99%
“…Kim and Dall'erba (2014) found a high spatial correlation of fossil fuel CO 2 emissions from crop production in the US; this might also apply to other GHG emissions in the agricultural sector. So, in advanced analysis, it is worth considering the correlation between some proxy data, for example, using tools of geostatistical modelling such as universal kriging (Young et al 2016) or autoregressive methods, and among them conditional (Horabik and Nahorski 2010) or spatial (Kim and Dall'erba 2014) autoregression models.…”
Section: Introductionmentioning
confidence: 99%
“…In another effort to merge model and satellite data, Lamsal et al (2008) was able to infer surface-level NO 2 concentrations from OMI NO 2 by applying local scaling factors from a global model. There has also been an emergence of a technique that combines land-use regression techniques with satellite information to infer ground-level NO 2 concen-trations (Novotny et al, 2011;Vienneau et al, 2013;Lee et al, 2014;Bechle et al, 2015;Young et al, 2016). While each individual technique is useful, all of the aforementioned techniques use model data to adjust existing satellite data but do not address issues inherent with the satellite retrieval methodology.…”
Section: Introductionmentioning
confidence: 99%